Experimental determination of dust cloud deflagration parameters of selected hydrogen storage materials: Complex metal hydrides, chemical hydrides, and adsorbents - Khalil, YF (Elsevier, 2012)
This paper discusses the results of an experimental program carried out to determine dust cloud deflagration parameters of selected solid-state hydrogen storage materials, including complex metal hydrides (sodium alanate and lithium borohydride/magnesium hydride mixture), chemical hydrides (alane and ammonia borane) and activated carbon (Maxsorb, AX-21). The measured parameters include maximum deflagration pressure rise, maximum rate of pressure rise, minimum ignition temperature, minimum ignition energy and minimum explosible concentration. The calculated explosion indexes include volume-normalized maximum rate of pressure rise (KSt), explosion severity (ES) and ignition sensitivity (IS). The deflagration parameters of Pittsburgh seam coal dust and Lycopodium spores (reference materials) are also measured. The results show that activated carbon is the safest hydrogen storage media among the examined materials. Ammonia borane is unsafe to use because of the high explosibility of its dust. The core insights of this contribution are useful for quantifying the risks associated with use of these materials for on-board systems in light-duty fuel cell-powered vehicles and for supporting the development of hydrogen safety codes and standards. These insights are also critical for designing adequate safety features such as explosion relief venting and isolation devices and for supplementing missing data in materials safety data sheets.